A Comparative Study of St Segment Resolution between Diabetic and Non-Diabetic ST Segment Elevation Myocardial Infarction Patients following Streptokinase Thrombolysis - Iqbal, Shahriar; Bari, M Saiful; Bari, MA; Islam, Mirza Md Nazrul; Majumder, M Abdullah Al Shafi; Islam, Zahidul; Aditya, Gana Pati; Paul, Gobinda Kanti; Shakil, Shiblee Sadeque; Saha, Bishwanath; Paul, Protap Kumar; Uddin, Mohammad Jalal (Cardiovascular Journal, 2019)
Background: One of the most effective and used (in our settings) methods of reperfusion of ST elevation myocardial infarction (STEMI) is administration of streptokinase (SK) infusion. This study was conducted with the aim to compare ST segment resolution between diabetic and non-diabetic patients with ST segment elevation myocardial infarction after thrombolysis by streptokinase. Methods: A total of 100 patients with ST elevation myocardial infarction with or without diabetes mellitus were studied from December 2016 to November 2017. Among these half of patients were diabetic while rests were non-diabetic. Streptokinase was administered to all patients. Resolution (reduction) of elevated ST segment was evaluated after 90 min of streptokinase administration. Results: Failed reperfusion (<30% ST resolution) was significantly higher in diabetic as compared to nondiabetic patients (42% vs. 12%, p <0.001). In hospital complications were more in diabetic patients who has failed reperfusion following streptokinase thrombolysis. Cardiogenic shock occurred in 44% and acute LVF in 30% patients and EF (46.54%) was significantly lower in diabetic patients and higher number of diabetic patients had prolong hospital stay than non-diabetic patients with STEMI. Conclusion: The outcome of thrombolytic therapy is adversely affected by diabetes mellitus in patients with ST-elevation myocardial infarction. Cardiovasc. j. 2019; 11(2): 118-122